BRIDGING THE KNOWLEDGE GAPS OF DEMENTIA AMONG YOUNG ADULTS THROUGH RADIO ENLIGHTENMENT CAMPAIGNS IN OYO STATE - Adebayo, John James; Bankole, Temidayo Olurotimi; Adediji, Moses Olumide (African Journal of Social and Behavioural Sciences, 2024)
This study examined knowledge gaps related to dementia among adults through radio enlightenment campaigns in Oyo State. Dementia is the fifth leading cause of death accounting for 2.4 million deaths globally, and age is the greatest risk factor for dementia. Given the growing aging population worldwide, the number of people who suffer dementia is increasing very year. The survey was chosen as the research design for this study, and it was used to determine older people’s opinions, attitudes and beliefs about issues of dementia in Oyo State. The study population consisted of adults who were affected by dementia. The findings showed that radio is less effective about dementia enlightenment campaigns. Findings showed that hospital-based enlightening campaigns about dementia have been effective in Oyo State. Hospital-based enlightening campaigns about dementia are not only trusted but questions can also be asked and immediate answers can be provided on the spot. The findings also showed that respondents preferred face-to-face health talks to radio enlightenment campaigns about dementia in Oyo State.